2014
DOI: 10.4236/jbbs.2014.43018
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects of Late Life Depression: Review of Neuropsychological Findings

Abstract: Normal aging and depression both slow information processing speed which leads to poorer attentional control, shallower inhibition monitoring, poorer encoding, poorer updating of short term memory, and subsequent poorer learning, set-shifting, error monitoring, inhibition control, and cognitive planning. A combination of aging and depression amplifies these cognitive effects. Deterioration in frontal brain functioning in normal aging is irreversible, but altering of frontal brain function due to depression may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 109 publications
(174 reference statements)
0
11
0
Order By: Relevance
“…An initial direct comparison of the emotional words vs neutral words condition (collapsed across group) yielded significant activations in several frontal and parietal regions, including bilateral MFG, right AI, left posterior insula, right ACC, right IFG, left DLPFC, bilateral fusiform gyrus, bilateral lingual gyrus, right supramarginal gyrus, left angular gyrus, left postcentral gyrus and left middle temporal gyrus. All of these regions have previously been reported in several studies using similar interference paradigms (Ochsner & Gross, 2005; Blasi et al ., 2007; Korsnes & Ulstein, 2014). The direct comparison of emotional vs neural words contrast between the two groups clearly demonstrates that healthy controls (HEC) showed greater activation in bilateral MFG, left DLPFC and left angular gyrus relative to LLD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial direct comparison of the emotional words vs neutral words condition (collapsed across group) yielded significant activations in several frontal and parietal regions, including bilateral MFG, right AI, left posterior insula, right ACC, right IFG, left DLPFC, bilateral fusiform gyrus, bilateral lingual gyrus, right supramarginal gyrus, left angular gyrus, left postcentral gyrus and left middle temporal gyrus. All of these regions have previously been reported in several studies using similar interference paradigms (Ochsner & Gross, 2005; Blasi et al ., 2007; Korsnes & Ulstein, 2014). The direct comparison of emotional vs neural words contrast between the two groups clearly demonstrates that healthy controls (HEC) showed greater activation in bilateral MFG, left DLPFC and left angular gyrus relative to LLD.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a recent meta-analysis study indicated that elderly patients with AD and higher CR exhibited greater activation in the anterior cingulate cortex (ACC) during cognitive tasks relative to those with lower CR (Colangeli et al ., 2016). These findings suggest that elderly individuals with higher levels of CR are more capable of recruiting alternative and/or additional brain networks to respond to cognitive changes due to pathological aging, especially within the prefrontal regions (Korsnes & Ulstein, 2014; Scarmeas & Stern, 2004; Stern et al, 2018b).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Improving cognitive functioning (information processing speed, attention control, short term memory, learning and cognitive planning, sensory discrimination) is important for diminishing the negative effects from depression [21,22]. Self-expression by means of overt and assertive behaviour, as well as self-realization give the possibilities for students' improved cognitive functioning in the academic environment [23], and aesthetic experiences in the learning process also contribute to positive emotions and further development of cognitive functioning by means of complex processing of information [24].…”
Section: Introductionmentioning
confidence: 99%
“…Support for the expectation that cognitive SOPT would have a beneficial downstream effect by reducing depressive symptoms is more exploratory and stems from two sets of empirical evidence. The first is the well-established association between processing speed and depression (Dybedal, Ranum, Sundet, Gaarden, & Bjolseth, 2013; Korsnes & Ulstein, 2014; McClintock, Husain, Greer, & Cullum, 2010; Thomas & O’Brien, 2008; van den Kommer et al, 2013). Because the etiology underlying that association remains contested, all of the authors cited above have concluded that additional study is needed.…”
Section: Introductionmentioning
confidence: 99%